2017
DOI: 10.1515/logos-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological investigations of river bed clogging at a river bank filtration site along the River Warta, Poland

Abstract: River bank filtration (RBF) is a system that enriches groundwater resources by induced infiltration of river water to an aquifer. Problematic during operation of RBF systems is the deterioration of infiltration effectiveness caused by river bed clogging. This situation was observed in the Krajkowo well field which supplies fresh water to the city of Poznań (Poland) during and after the long hydrological drought between the years 1989 and 1992. The present note discusses results of specific hydrogeological rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…For pesticides and pharmaceuticals, 6 sampling series were planned at all sampling points located on the transects. In this article, the preliminary results from [20]. Legend: 1-the embankment; 2-sands; 3-gravels; 4-silts; 5-clays; 6-the static and dynamic water level; 7-groundwater flow directions; 8-the position of the RBF well screen; 9-the position of the HW drains; 10-other observation wells; 11-Quaternary; 12-Neogene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For pesticides and pharmaceuticals, 6 sampling series were planned at all sampling points located on the transects. In this article, the preliminary results from [20]. Legend: 1-the embankment; 2-sands; 3-gravels; 4-silts; 5-clays; 6-the static and dynamic water level; 7-groundwater flow directions; 8-the position of the RBF well screen; 9-the position of the HW drains; 10-other observation wells; 11-Quaternary; 12-Neogene.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, only the portion of the well group shown in Figure 1 (RBF-f) was continuously pumped for a period of two years. [20]. Legend: 1-the embankment; 2-sands; 3-gravels; 4-silts; 5-clays; 6-the static and dynamic water level; 7-groundwater flow directions; 8-the position of the RBF well screen; 9-the position of the HW drains; 10-other observation wells; 11-Quaternary; 12-Neogene.…”
Section: Site Descriptionmentioning
confidence: 99%
“…The solution of the problem is associated with the clearing of fine earth in the channels of watercourses and its transportation to the dump. The most rational way to restore the channels is to clear sediment layers by dredgers, which supply them to the disposal sites to form natural coastline [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…It has been used along the Rhine and Elbe Rivers in Germany for over 140 years (Becker et al 2015). In several European countries, RBF is commonly used such as Poland, France, Netherlands (Przybyłek et al 2017), also, the United States (Kelly et al 2006). In addition to applying in west Asia, in China, where evaluation the suitability of RBF along the Second Songhua River (Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%